Optimizing Ketamine-Propofol Collaboration to Prevent SpO₂ Decrease in TIVA Patients at RSU Emanuel Banjarnegara - Rahmaya Nova Handayani; Sakhfa Syesar Novaliyanto; Surtiningsih (Jurnal Penelitian Pendidikan IPA, 2025)
Total Intravenous Anesthesia (TIVA) is a widely used anesthetic technique that relies entirely on intravenous agents. However, one of its challenges is the potential reduction in oxygen saturation (SpO₂) during induction. Ketamine and propofol are commonly used anesthetic agents and their combination is hypothesized to optimize hemodynamic stability and prevent SpO₂ decline. Objectives: This study aims to evaluate the effectiveness of ketamine-propofol collaboration in maintaining oxygen saturation during TIVA induction at RSU Emanuel Banjarnegara. Methods: This study was a quasi-experimental study with 50 TIVA patients who met the inclusion criteria. Result: The study found that patients receiving the ketamine-propofol combination exhibited a more stable SpO₂ level compared to those receiving propofol alone. The mean decrease in SpO₂ was significantly lower in the combination group (p < 0.05), indicating the protective effect of ketamine in preventing hypoxia. The combo group also maintained hemodynamic indicators including blood pressure and heart rate better. Conclusion: The simultaneous injection of Ketamine and Propofol is beneficial in preventing a drop in SpO₂ 1 minute after induction of anesthesia compared to the combination of Propofol alone.